Pengaruh Struktur Modal dan Pertumbuhan Penjualan Terhadap Kinerja Keuangan dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Venny Amanda Winanty; Eli Safrida; Jojor Lisbet Sibarani (Politeknik Ganesha Medan, 2025)
This study aims to determine the effect of capital structure and sales growth on financial performance, with company size as a moderating variable, in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX). This research is supported by Signaling Theory, which explains that financial information conveyed by management through financial reports provides signals to investors regarding the company's condition. The data used are secondary data, consisting of financial reports from consumer goods companies for the 2020–2024 period. The sample was determined using a purposive sampling method, resulting in 220 observations from 44 companies over a five-year period. Data analysis was conducted using descriptive statistics, while hypothesis testing used moderated regression analysis (Moderated Regression Analysis) with the help of SPSS version 27. The results indicate that capital structure has a negative and significant effect on financial performance, such that an increase in capital structure tends to decrease financial performance. Conversely, sales growth has no significant effect on financial performance. Furthermore, company size does not moderate the effect of capital structure or sales growth on financial performance, so company size does not change the strength of the influence of these two independent variables.